Penerapan Manajemen Kepala Ruangan di Ruang Rawat Inap RSUD Kabupaten Majene - Lamukara, Iin Utami Yasrianti; Sudarman, Sudarman; Haeril Amir (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2023)
The leadership of the head of the room reflects the quality of health services in the hospital. This study aimed to analyze the application of head management in the inpatient ward of RSUD Kab. Majene. This research analyzes results and implementation gaps using a literature review. Data were taken through questionnaires on 120 nurse respondents. The data were analyzed descriptively by looking at the room head management analysis frequency distribution. The results showed that the application of the head of the room management related to the planning function was 78.3%, the organizing function was 62.5%, the directive function was 83.3%, the control and supervision function was 72.5%, and the evaluation function was 66.7. %. The conclusion of implementing the management of the head of the room was carried out well.